2013
DOI: 10.1111/tbj.12148
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction National Trends and Healthcare Implications

Abstract: Breast reconstruction improves quality-of-life of breast cancer patients. Different reconstructive options exist, yet commentary in the plastic surgery literature suggests that financial constraints are limiting access to autologous reconstruction (AR). This study follows national trends in breast reconstruction and identifies factors associated with reconstructive choices. Data were obtained from the Nationwide Inpatient Sample from 1998 to 2008. Patients were categorized as having either implant or ARs. Biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 53 publications
(72 reference statements)
3
57
1
Order By: Relevance
“…10 Furthermore, Medicare physician payments from 1998 to 2008 have declined by only 4 percent for implants, whereas they have decreased by 11 percent for autologous tissue transfers. 11 These effects are magnified by the adoption of lengthier microsurgical techniques, particularly in the setting of bilateral mastectomy defects. 12 The high proportion of U.S. gross domestic product spending on health care is one factor that motivated passage of the Affordable Care Act, with the aims of reducing cost and maximizing quality.…”
mentioning
confidence: 99%
“…10 Furthermore, Medicare physician payments from 1998 to 2008 have declined by only 4 percent for implants, whereas they have decreased by 11 percent for autologous tissue transfers. 11 These effects are magnified by the adoption of lengthier microsurgical techniques, particularly in the setting of bilateral mastectomy defects. 12 The high proportion of U.S. gross domestic product spending on health care is one factor that motivated passage of the Affordable Care Act, with the aims of reducing cost and maximizing quality.…”
mentioning
confidence: 99%
“…1,2,16 Although the present study confirms that implant-based reconstructions are still the preferred method for primary reconstruction in academic institutions, the trend toward their increasing use year to year has tapered. The most notable finding of the present study is the prominence of microsurgical reconstruction and revision reconstruction in academic settings (Fig.…”
Section: Discussionmentioning
confidence: 47%
“…1 Immediate reconstructions, mostly implant based, also increased by 5% yearly, with a near-doubling reported in a Surveillance, Epidemiology, End-Results database analysis. 2 Associated with this trend, a growing incidence of elective mastectomy and contralateral prophylactic surgery in lieu of breast conservation has been described in several large studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a study 13 demonstrated that the number of IBR increased 11% per year from 1998 to 2008. During the same period, it was also noted that the number of autologous reconstructions decreased 5% per year.…”
Section: Discussionmentioning
confidence: 99%